ChemInform Abstract: Organic Stereochemistry. Part 8. Prostereoisomerism and the Concept of Product Stereoselectivity in Biochemistry and Xenobiotic Metabolism. Issue 42 (1st October 2013) - Testa, Bernard
Abstract Review: 114 refs.